2022
DOI: 10.1093/jnci/djac153
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Caregivers’ Burden When Caring for Patients With Pancreatic and Periampullary Cancer

Abstract: Background Family and other unpaid caregivers play an active role in the recovery of individuals with pancreatic and periampullary cancer after pancreatectomy. However, little is known about caregivers’ experiences and how to better support them. Methods Caregivers accompanying patients to one-month post-pancreatectomy visits at 3 hospitals completed an electronic survey between November 2018 - February 2020. We examine measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…A sobering finding was that quality of communication and capacity assessment by caregivers were not associated with their outcomes (financial, emotional, and physical well-being). In other 13,35 The CAPACITY instrument had excellent internal consistency within the two domains of communication and capacity when applied to our study population. The CAPACITY instrument was initially developed and validated in a population of veterans with disabilities.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…A sobering finding was that quality of communication and capacity assessment by caregivers were not associated with their outcomes (financial, emotional, and physical well-being). In other 13,35 The CAPACITY instrument had excellent internal consistency within the two domains of communication and capacity when applied to our study population. The CAPACITY instrument was initially developed and validated in a population of veterans with disabilities.…”
Section: Discussionmentioning
confidence: 71%
“…11,12 Their ability to provide care may be diminished by competing priorities, such as full-time employment or childcare needs. 13,14 It has been hypothesized that improving the quality of communication and an assessment of the capacity of caregivers can enable their caregiving role and improve the quality of their caregiving. Potential mechanisms include increasing the caregiver's clinical, support-seeking, and psychological skills, as well as strengthening the caregiver's therapeutic alliance with the health care team.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 In this setting, a considerable amount of patient care responsibility has been shifted onto family and unpaid caregivers who presently serve as a considerable workforce even when patients are in rehabilitation and residential care facilities. 23,24 A recent study demonstrated that social support was associated with decreased health care utilization and improved overall survival in patients with hematologic malignancies. 25 Another study demonstrated that having social support was positively associated with the odds of receiving chemotherapy in patients with advanced colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Ashghali Farahani et al (2021) define the burden of care as the caregiver's physical, mental, and social reactions which arise from the imbalance between care needs and other caring tasks. Caregiver burden is associated with adverse outcomes for both caregivers and patients, including a reduction of general health and quality of life (Seidel & Thyrian, 2019), and an increase in risk for patient morbidities (Sari et al, 2018), which is a multidimensional response to perceived stress and negative assessments that derive from providing care to a patient (Fong et al, 2022).…”
Section: Introductionmentioning
confidence: 99%